Association between healthy eating index-2015 and abdominal aortic calcification among US Adults - Jia, Jundi; Zhang, Jie; Ma, Dan; Zhang, Zihao; Zhao, Lin; Wang, Tongxin; Xu, Hao (Frontiers in Nutrition, 2023)
Aims To evaluate the relationship of healthy eating index-2015 (HEI-2015) with the abdominal aortic calcification (AAC) in the US adults. Methods We conducted a cross-sectional study with data extracted from the National Health and Nutrition Examination Survey (NHANES). AAC score was measured using score system of Kauppila (AAC-24) and Schousboe (AAC-8). HEI-2015, which was used for evaluating the compliance with Dietary Guidelines for American (DGA), was calculated through two rounds of 24-hour recall interviews. HEI-2015 was categorized as inadequate (<50), average (50~70) and optimal (≥70) group for analysis, while the AAC-24 score was grouped by whether the score was > 0. Weighted multiple regression analyses were conducted to estimate the association of HEI-2015 with AAC score and the presence of AAC. Moreover, smooth curve fittings, based on generalized additive model (GAM), were applied to evaluate a possible non-linear relationship. Sensitivity analysis and subgroup analysis were performed to provide more supporting information. Results A total of 2704 participants were included in the study (mean age, 57.61 ± 11.40 years; 51.78 % were female). The mean score of HEI-2015 was 56.09 ± 13.40 (41.33 ± 6.28, 59.44 ± 5.54, and 76.90 ± 5.37 for inadequate, average and optimal group, respectively). After adjusting for covariates, higher HEI-2015 was associated with decreased AAC score (AAC-24: β =-0.121 , 95％CI -0.214, -0.028, P=0.010; AAC-8: β=-0.054, 95％CI -0.088, -0.019, P=0.003), and lower risk of AAC (OR =0.921, 95％CI 0.855, 0.993, P=0.031). Among the components of HEI-2015, higher intake of fruits, greens and beans was associated with lower AAC score. Subgroup analysis showed that an inverse association of HEI-2015 with AAC score existed among different groups. Conclusion The study presented that higher HEI-2015 was related to lower AAC score and decreased risk of having AAC, indicating that greater compliance with 2015-2020 DGA, assessed by HEI-2015, might be beneficial for preventing vascular calcification and CVD among US adults.